The Organic Arsenic Compound Diphenylarsinic Acid Transfers From the Mother to the Fetus via the Placenta in Mammals - Tomoyuki Masuda; Kazuhiro Ishii; Tomohiro Nakayama; Nobuaki Iwasaki (Neuropsychopharmacology Reports, 2025)
ABSTRACT Background In 2003, contamination of drinking well water with diphenylarsinic acid (DPAA), an organoarsenic compound not naturally found in the environment, was reported in Kamisu City, Ibaraki Prefecture, due to suspected illegal dumping. Residents in the surrounding area, including pregnant women, were exposed to DPAA, leading to health issues primarily affecting the central nervous system. However, the extent of DPAA transfer from pregnant women to their fetuses remains unknown. Methods The concentration of DPAA in preserved dried umbilical cords from pregnant women who had consumed DPAA‐contaminated well water was measured using liquid chromatography–tandem mass spectrometry. Additionally, pregnant rats (n = 9) were orally administered DPAA (0.25, 0.5, or 1.0 mg/kg/day) for 13 days. Fetuses (five per mother, n = 45) were delivered, and the DPAA concentrations in maternal and fetal blood, as well as in the brain, were measured. Results The DPAA concentration in fetal blood was 30.0%–40.1% of that in maternal blood, regardless of the administered dose. On the other hand, the DPAA concentration in the fetal brain was 8.31%–9.00% of that in the maternal brain, independent of the administered DPAA dose. Conclusion The analysis of umbilical cords from pregnant women who drank water containing DPAA revealed that DPAA could transfer from the mother to the fetus through the placenta. Additionally, experiments using rodents confirmed that DPAA could also reach the fetal brain through placental transfer, but the transfer rate was low.